SOSIALISASI PARENTING ANAK PADA IBU-IBU PKK DI DUKUH SAMBIROTO,DESA SINDON KABUPATEN BOYOLALI - Ima Nia Uliasari; Faqih Purnomosidi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Parenting is the pattern of parenting of parents towards children which influences the child's growth and development, the formation of attitudes and character. Every parent is obliged to care for and love their child. Because basically, every child needs guidance and direction from every parent from the time they are still in the womb until the child understands the meaning of life. Parenting or the parenting style of parents towards children, namely, meeting physical needs, namely food and drink, and also fulfilling psychological needs, namely love, attention, comfort, security, and socializing with the surrounding community so that children can live in harmony with their environment. Most of a child's life span is within the family, therefore parents' parenting patterns towards children greatly determine and influence the child's personality and behavior (child's character). As time goes by, parents' parenting patterns for children are decreasing and decreasing, most parents are busy at work so they cannot hinder children's optimal growth and development. Apart from being busy with work, many parents do not understand parenting, how to properly raise children, which is in accordance with religious values ??and social morals, most parents see that children, after entering adolescence, are considered capable of managing and taking care of their children. their own lives so that many children have the wrong relationships due to lack of parental control in children's growth and development and children's character education. Knowledge about Dukuh Sambiroto Parenting is also still lacking, therefore there is a need for socialization regarding the importance of parenting in character building in children so that children can grow and develop into individuals with character, have commendable behavior, polite speech, politeness in speaking and good impression on himself, his family and society